SURGICAL TACTICS AND CHOICE OF PHARMACOTHERAPY FOR STENOSING PYLORODUODENAL ULCERS - Nishonov, F.N; Nishonov, M.F (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
To improve the results of surgical treatment of patients with stenosing pyloroduodenal ulcers. Material and Methods: the results of the examination and surgical treatment of 223 patients with peptic ulcer complicated by pyloroduodenal stenosis, who underwent various types of gastrectomy, and 32 patients with stenotic pyloroduodenal ulcers, who underwent excision of the stenotic ulcer with plastic operations of the pyloroduodenal zone to normalize evacuator, were analyzed. stomach. Results: Thanks to the use of the complex of measures developed by us, before, during and after surgery, good results were obtained in patients of the main group: the number of complications specific to operations on the stomach decreased to 9.75%; general postoperative complications - up to 7.31%; all patients recovered, there were no deaths. The duration of hospital stay is 9.2 days. Conclusions: Improved methods of economical resection of the stomach with excision of the omentum, preferential completion of the gastroduodenal anastomosis imposing reduces the aggressiveness of the peptic factors of the gastric juice and normalize the evacuation function of the stomach, which contributes to the rapid normalization of disturbed functions of the stomach and duodenal ulcer.